Modeling and Optimization of Co-TDMA in Next-Generation Wi-Fi Systems Based on Optimal Transportation Theory - Junxiong Zhang; Weimin Wu; Xiaohu Ge; Yingzhuang Liu (IEEE Open Journal of the Communications Society)
The importance and commercial value of wireless fidelity (Wi-Fi) technology are now widely recognized. However, the traditional Wi-Fi technology causes the throughput of access points (APs) to quickly approaches a saturated level when the number of accessing stations (STAs) is large than a specified threshold. To improve the saturated throughput of APs, a new multi-AP cooperative architecture assisted by a centralized AP controller is proposed. Based on the proposed architecture, a new channel access mechanism called optimal transportation channel access (OTCA) mechanism is proposed to reduce the collision among STAs in Wi-Fi networks. Based on the modulation and coding scheme, a subordinate AP negotiates with the STA to confirm the STA transmission rate in OTCA mechanism. Moreover, the subordinate AP reports the confirmed transmission rate to the centralized AP controller. The centralized AP controller distributes data to the associated subordinate AP based on the optimal transportation theory. Considering the latency constraint, a new algorithm called optimal transportation (OT) algorithm is developed to adjust the STA data volume for associated subordinate APs and improve the throughput of Wi-Fi networks. Compared to the traditional enhanced distributed channel access algorithm, simulation results indicate that the OT algorithm reduces the average latency by 14.14% and improves the average throughput by 21.90%.